2009
DOI: 10.1016/j.psc.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Research Ethics Issues in Geriatric Psychiatry

Abstract: SynopsisWith an aging population, and the prevalence of psychiatric illness in the older population expected to rise dramatically in coming decades, advances in geriatric psychiatry research are urgently needed. Ethical issues in the design, conduct, and monitoring of research involving older adults parallel these same issues related to human subjects research generally. Yet a number of special issues relevant to geriatric psychiatry research merit further discussion. These special issues include the assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Of the 80 articles, 16 were essay-type articles 16,20,23,27,30,33,37,42,64,65,67,68,71,72,81,91 ; 7 were surveys 18,19,46,47,73,75,85 ; and 57 were research articles consisting of case studies and case reports, follow-up studies, cross-sectional studies, case-control and cohort studies, randomized trials, and systematic reviews. 1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 80 articles, 16 were essay-type articles 16,20,23,27,30,33,37,42,64,65,67,68,71,72,81,91 ; 7 were surveys 18,19,46,47,73,75,85 ; and 57 were research articles consisting of case studies and case reports, follow-up studies, cross-sectional studies, case-control and cohort studies, randomized trials, and systematic reviews. 1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Decision-making capacity, 1 of the principle pillars of valid informed consent, has 4 essential domains: understanding relevant information, appreciating and applying the information to one’s personal needs and circumstances, rational reasoning, and communicating a clear and consistent choice. 30 Even though the MMSE and MacCAT for Clinical Research were the most studied capacity assessment tools, investigators in few studies reported using them in everyday practice. The tools were time-consuming to use and insufficient to determine the degree to which patients possess the capacity to provide valid consent.…”
Section: Discussionmentioning
confidence: 99%
“…Writing on research ethics in geriatric psychiatry, Dunn and Misra [34] warn that, unless work is done to clarify the issues surrounding proxy consent and incapacitated persons, 'deleterious effects on research can result' which includes research bans and over-protection as well as inaccurate weighing of risks and benefits (p. 395). These authors' concerns mirror those of Fins' for the case of patients with severe DOC.…”
Section: The Role Of Surrogatesmentioning
confidence: 99%
“…36 Indeed, concerns have persisted for decades regarding the ethical acceptability of including people with different illnesses or have characteristics that may make them especially vulnerable in the context of human studies. 1719 …”
Section: Introductionmentioning
confidence: 99%